English First Additional Language: Teachers’ written feedback practices in multi-grade classrooms in rural South African primary schools - Matshidiso Joyce Taole (South African Journal of Education, 2022)
Multi-grade teaching is a widely accepted phenomenon in both developing and developed countries. In this article I report on a phenomenological inquiry into written feedback practices of teachers in multi-grade classrooms and how they described and interpreted their feedback practices pertaining to learners’ writing activities in English First Additional Language. Written feedback is widely believed to be central to learners’ learning and achievement. Feedback is assumed to change learners’ thinking or behaviour towards their work and is regarded as a tool to focus their attention on improving their learning. Despite the benefits of written feedback, however, there is a widespread belief that many learners are disengaged from the feedback they receive. The population in this study comprised 4 English First Additional Language teachers from 4 multi-grade primary schools. Content analysis was used to analyse the data collected from the participants through semi-structured interviews. The findings indicate that participants differed in their understanding of what was involved in feedback, and that there was a shared view that feedback was a product and not viewed as a process that could be used towards developing learners’ learning. It was also shown that feedback practices used by the teachers of multi-grade classes included providing correct answers and providing delayed feedback to learners. This study adds to the ongoing debates on multi-grade teaching and attempts to shed some light on the nature and the type of feedback that could motivate and enhance learners’ learning in multi-grade classrooms.